Genetic diversity of Fusarium spp. isolated from fruit rot of banana in Peninsular Malaysia - Abd Murad, Nur Baiti (2017)
Banana ranks first in global fruit production and economic source for the producing countries, however, bananas are always at high risk for fungal infection dominantly by Fusarium species in the field and post-harvest stages. Hence, this study was conducted to understand the etiology of fruit rot disease on banana. The objectives of this study were to isolate and identify the isolates of Fusarium species based on gene encoding translation elongation factor 1-α (tef1-α) sequence and phenotypic analysis, to determine genetic diversity among isolates and species of Fusarium using selected microsatellite markers and to examine pathogenicity of the Fusarium isolates in causing fruit rot disease of banana. The justification of the first objective was to provide the information ofFusarium species associated with fruit rot disease of banana in Peninsular Malaysia, while for the second objective was to examine the genetic diversity that maybe varies among the individual isolates of the Fusarium spp. and for the third objective was to observe the ability of individual isolates of the Fusarium spp. to cause fruit rot disease on the inoculated banana fruits in order to fulfil the Koch’s Postulate principles. A series of sampling was conducted throughout Peninsular Malaysia and fungal species identification was conducted based on morphological and gene encoding tef1-α sequence analysis. Eleven species of Fusarium were discovered namely Fusarium incarnatum, Fusarium equiseti, Fusarium camptoceras, Fusarium solani, Fusarium concolor, Fusarium oxysporum, Fusarium proliferatum, Fusarium verticillioides, Fusarium sacchari, Fusarium concentricum and Fusarium fujikuroi.The genetic diversity of the Fusarium isolates was studied using six selected established microsatellite primers for Fusarium species. The results showed that all the Fusarium isolates were grouped into their respective clades, indicated their similarity and differences in genetic diversity among isolates and species. All 48 Fusariumisolates were tested for pathogenicity test by inoculating fungal disc on unwounded banana fruit. The results showed that all Fusarium species were causing fruit rot symptom at different level of severity based on Disease Severity Index (DSI) except for non-pathogenic isolates of F. solani (isolates B2385 and B2432), F. oxysporum (isolate J2421), F. sacchari (isolates B2426 and B2427) and F. equiseti (isolate B2361). The most virulent isolate was F. proliferatum (isolate B2433) with DSI of 100%. The non- inoculated controls showed no symptom of fruit rot. In conclusion, F. incarnatum F. solani F. proliferatum,F. verticillioides,F. oxysporum,F. sacchari,F. camptoceras, F. concentricum, F. fujikuroi, F. concolor and F. equiseti were successfully identified and some of the Fusarium species were confirmed as causal agents of pre- and post-harvest fruit rot on banana in Malaysia.